On-farm evaluation of dry-seeded rice cultivars and cropping systems in the semi-arid region of India - Soriano, Junel B.; Wan, Suhas P.; Rao, Adusumilli N.; Hanumanthappa, Anantha K.; Gowda, Jnanesha A.C.; Rathore, Abhishek (2017)
Improving and sustaining rice-based cropping systems in the semi-arid region are essential in persistent drought condition triggered by worsening effects of climate change and declining water availability. This on-farm study was conducted to evaluate and identify the most productive, resource efficient and profitable direct dry-seeded rice (DDSR) cultivars, and DDSR-based cropping systems in the semi-arid region particularly in water-short irrigated rice areas. Farmer participatory field studies were conducted in Raichur District of Karnataka State, India to assess the performance of DDSR cultivars (Samba Mahsuri, Gangavathi Sona and Prasanna) seeded during the rainy season in rotation with dryland crops (chickpea, mustard and green gram) following rice. Among the three rice cultivars, Gangavathi Sona yielded 9% and 15% higher than Samba Mahsuri and Prasanna, respectively. Our study showed that productivity of rice can be improved by using drought resistant and high yielding cultivars with high harvest index, and stable canal water supply at the reproductive stage. Chickpea and green gram yielded better than mustard under minimal soil aeration conditions of zero-tilled and non-puddled fields which indicate that suitable post-rainy season crops for zerotilled fields must be selected. The study revealed that sowing time, which depends on rainfall pattern and schedule of canal water supply, is among the major factors to be considered in selecting rice cultivars and dryland crops to achieve higher productivity, resource use efficiency and economic returns. Cropping system involving direct dry-seeding of Gangavathi Sona, followed by chickpea achieved higher production efficiency, land and water productivity, and economic returns compared to transplanted rice (TPR) system. Improving the productivity of chickpea and other suitable dryland crops that can be grown after rice in zero-tilled fields will contribute substantially to the evolving impacts of DDSR-based cropping systems in the semi-arid region. (Author's abstract)
Includes bibliographical references (pages 233-235)
Keywords: Agriculture; Cropping system; Direct dry-seeded rice; Dryland crops